Analisis Daya Saing Ekspor Karet Alam (Natural Rubber) Indonesia di Pasar Internasional - Yogi Rahmad Syahputra; Suardi Tarumun; Jumatri Yusri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this study was to analyze the development of Indonesia's natural rubber exports and analyze the competitiveness of Indonesian natural rubber in the international market. The data used in this study was a secondary data export raw natural rubber Indonesia, Thailand, and Malaysia during the period 1996-2010. The data was taken from the value and volume of exports of natural rubber in the international market. The analytical method used was the Revealed Comparative Advantage ( RCA ) and Constant Market Share ( CMS ). The results of this study indicate that the development of Indonesia's natural rubber exports tend to increase every year. The level of the comparative advantage of Indonesia's natural rubber exports relatively higher than Malaysia. Meanwhile during the period 1996-2006, the level of the comparative advantage of Indonesia was lower than Thailand. While during the period 2007-2010, the level of the comparative advantage of Indonesia's natural rubber is relatively higher than Thailand. This data indicated that Indonesia has a comparative advantage exports of natural rubber were getting better every year. From the CMS analysis note that the competitiveness of Indonesia's natural rubber exports more influenced by standard growth and competitiveness effects. This represents an increase of Indonesia's natural rubber exports more influenced by the growth of the world's natural rubber exports. Additionally, Indonesia also exports natural rubber has high competitiveness due to the excellence of product quality or better price. Keywords: natural rubber, competitiveness , Revealed Comparative Advantage ( RCA ) , Constant Market Share ( CMS )